Clinicopathological spectrum of ovarian cystic lesions with ultrasonographic correlation in a tertiary care hospital in Nepal - Gauli, Bandana; Pun, Chin Bahadur; Goyal, Binita; Shrestha, Akshunna Rup (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Cystic lesions of the female genital tract, especially ovarian cysts, range from functional to malignant. While ultrasonography aids initial evaluation, histopathology is the gold standard. This study aimed to assess the histopathological spectrum and its correlation with imaging and clinical findings.Materials and Methods: This analytical cross-section study was carried out among 33 cases presenting as cystic masses from October 2022 to September 2023. For histopathological analysis, the specimens were grossed, processed, and embedded using standard procedures. For inferential statistics, Cohen’s Kappa was calculated to access agreement between imaging and histopathological diagnosis as well as sensitivity, specificity and diagnostic accuracy of imaging studies.Results:   Out of 33 cases, the maximum number, 14 (36.7%), belonged to the 21– 40-year age group. Among the clinical features, incidental findings accounted for the largest proportion, seen in 15 (45.5%) patients. Histopathological evaluation classified the lesions into non-neoplastic, 21 (63.3%), and neoplastic 12 (36.7%). Follicular cyst, 8 (24.2%), emerged as the predominant non-neoplastic lesion, while mature cystic teratoma, 5 (15.4%), was the most common among neoplastic lesions.Conclusions: Most ovarian cystic lesions are benign and non-neoplastic in nature and occur predominantly in women of reproductive age.  Histopathology was found to have moderate degree of aggregability with imaging findings. However, due to high specificity and moderate sensitivity of imaging findings, it can be used as a good adjunct tool along with histopathology for ruling in the disease if any clinical suspicion arises.